Isolation, biological activity and secondary metabolite investigations of marine-derived fungi and selected host sponges - Höller, Ulrich (1999)
Higher filamentous fungi were isolated from marine sponges and algae. Their taxonomy, the biological activity of their extracts, their secondary metabolite production, and the biological activity of the obtained pure compounds were investigated. Additionally, selected sponge samples were investigated chemically. Out of 16 sponge samples from six different locations, Australia (Bear Island and The Great Barrier Reef), Dominica (Caribbean), Helgoland (North Sea, Germany), Malta and Tenerife (Spain), 681 fungal strains, representing 53 genera (38 genera of mitosporic fungi, including two clearly obligate marine fungi, 13 genera of Ascomycetes, two genera of Zygomycetes), and 37 strains of Mycelia sterilia, were isolated. Representatives of most of these fungal genera have thus far not been reported from marine sponges. The taxonomy and diversity of the isolated fungal strains suggested, however, that the majority of them were not associated with the host-sponge, but had been simply filtered from the sea water. These isolates were most likely to be mainly terrestrial and facultative marine species. In order to enable preliminary investigations of their biologically active secondary metabolite production, 92 sponge-derived fungal strains were chosen for small scale cultivation on different media. EtOAc extracts of 75 strains (81.5 ) showed antimicrobial activity in agar diffusion assays for antibacterial, antifungal and antialgal activity. Extracts of 27 strains were further tested in different assays: Extracts of six strains showed significant cytotoxicity towards KB cells, and further six exhibited prominent Mycobacterium tuberculosis inhibition. HIV-1 reverse transcriptase was inhibited by extracts of eight strains, and tyrosine kinase (p56lck) by extracts of seven strains. Aus marinen Schwämmen und Algen wurden höhere, myzelbildende Pilze isoliert. Die Taxonomie der Isolate, die biologische Aktivität ihrer Extrakte, ihre Sekundärstoffproduktion und die biologische Aktivität der erhaltene Reinsubstanzen wurden ...